1982
DOI: 10.3382/ps.0611021
|View full text |Cite
|
Sign up to set email alerts
|

Daily Feed Intake and Performance of Laying Hens Grouped According to Their Body Weight

Abstract: Two experiments were conducted to investigate the relationship of laying hen body weight at 28 weeks to daily feed intake (DFI) and hen performance. Significant differences in the body weight of hens in the various body weight groups (BWG) were found at the beginning and end of the experiments. The differences in body weight were found to be related to DFI which increased in a linear fashion as body weight increased. It was found that 6.80 and 6.56 g more feed was consumed daily by each hen for each 100 g of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 0 publications
7
29
0
9
Order By: Relevance
“…The effect of body weight on FCR was found significant, and hens in L group had the lower FCR value than M and H groups. In agreement with the present results, Harms et al (1982) reported that feed consumption per kg of egg production increased as the body weight increased. Feed conversion ratio was not affected by weight group by age period interaction.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The effect of body weight on FCR was found significant, and hens in L group had the lower FCR value than M and H groups. In agreement with the present results, Harms et al (1982) reported that feed consumption per kg of egg production increased as the body weight increased. Feed conversion ratio was not affected by weight group by age period interaction.…”
Section: Discussionsupporting
confidence: 82%
“…Egg production was not affected by body weight. Similarly to the present study, other studies reported no change in egg production depending upon body weight (Harms et al, 1982;Cerolini et al, 1994;Harms et al, 2000;Kirikci et al, 2004). However, Harms and Russell (1996) and Akbas and Takma (2005) found that body weight was positively related to egg production.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…3, were from 10.95 to 11.65 g. Same range values determined from different studies that used the same age control groups (Dikmen and Ipek, 2006;Altan et al, 1998). The selection studies for body weight gain in poultry illustrated that there were increases in both egg weight and feed consumption (Harms et al, 1982;Leeson and Summers, 1987;Inal et al, 1996). On the other hand, Cherry et al (1987) reported that there were no significant differences for yolk proportion of eggs with low body weight and normal lines in chickens; these results were consistent with our study.…”
Section: Resultsmentioning
confidence: 99%